Legal Uncertainty of Sentana Men in Nyentana Divorce Inheritance : Ketidakpastian Hukum Kedudukan Sentana Men dalam Pewarisan Akibat Perceraian Nyentana - Gracea Inggrid Michellani; Tjempaka Tjempaka (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Balinese customary law regulates marriage, kinship, and inheritance through a patrilineal system that assigns inheritance rights and customary obligations primarily to men as purusa. Specific Background Nyentana marriage constitutes a customary deviation in which a man enters the wife’s family lineage and relinquishes his original kinship status, creating distinct legal consequences within Balinese customary law. Knowledge Gap Despite its practice, Balinese customary law does not clearly regulate the legal status and inheritance position of sentana men following divorce, resulting in normative ambiguity across customary communities. Aims This study examines the legal standing and inheritance rights of sentana men whose nyentana marriages end in divorce under Balinese customary law. Results The findings show that sentana men are regarded as having exited their original family and do not automatically regain purusa status after divorce, leading to the absence of inherent inheritance rights from either family lineage. In practice, inheritance from the original family may occur only through discretionary family agreement and customary acceptance. Novelty This research highlights persistent legal uncertainty in post-divorce customary status and inheritance positioning of sentana men within nyentana marriage structures. Implications The study underscores the need for clearer customary regulations to prevent legal vulnerability and disputes concerning inheritance and customary obligations in Balinese society. Highlights: Divorce in nyentana marriage does not restore former customary kinship status. Post-divorce inheritance claims lack uniform customary regulation. Family discretion determines possible asset allocation outcomes. Keywords: Nyentana Marriage, Balinese Customary Law, Inheritance Rights